Plasma membrane H+-ATPase overexpression increases rice yield via simultaneous enhancement of nutrient uptake and photosynthesis - Zhang, Maoxing; Wang, Yin; Chen, Xi; Xu, Feiyun; Ding, Ming; Ye, Wenxiu; Kawai, Yuya; Toda, Yosuke; Hayashi, Yuki; Suzuki, Takamasa; Zeng, Houqing; Xiao, Liang; et al. (Nature communications, 2021)
Nitrogen (N) and carbon (C) are essential elements for plant growth and crop yield. Thus, improved N and C utilisation contributes to agricultural productivity and reduces the need for fertilisation. In the present study, we find that overexpression of a single rice gene, Oryza sativa plasma membrane (PM) H + -ATPase 1 ( OSA1 ), facilitates ammonium absorption and assimilation in roots and enhanced light-induced stomatal opening with higher photosynthesis rate in leaves. As a result, OSA1 overexpression in rice plants causes a 33% increase in grain yield and a 46% increase in N use efficiency overall. As PM H + -ATPase is highly conserved in plants, these findings indicate that the manipulation of PM H + -ATPase could cooperatively improve N and C utilisation, potentially providing a vital tool for food security and sustainable agriculture. Improved utilisation of nitrogen and carbon could boost agricultural productivity. Here Zhang et al. show that overexpression of a single gene, encoding the plasma membrane H + -ATPase 1 OSA1, is able to increase both carbon fixation via photosynthesis and nitrogen assimilation via ammonium uptake in rice.